Strategic Financial Drivers of Sustainable Financial Performance: A Conceptual Study of AI Integration in Industrial Sector Companies in Oman - Kala, Pasala Vamsi; Podile , Dr. Venkateswara Rao; Narapareddi , Dr. N. Visalakshi (International Journal of Accounting and Economics Studies, 2025)
This empirical study investigates the strategic financial drivers influencing sustainable financial performance in industrial sector companies in Oman, with a particular emphasis on the theoretical contribution of AI integration in financial decision-making. Amid growing global pressures for economic, environmental, and social sustainability, industrial firms, often characterized by capital-intensive operations and complex financial structures, face unique challenges in aligning profitability with long-term sustainability goals. The study focuses on three core financial variables: financial leverage, working capital management, and dividend policy, assessing their individual and collective impacts on sustainable financial performance, measured through Return on Assets and Environmental, Social, and Governance disclosures. In addition to traditional financial drivers, the research conceptualizes the role of Artificial Intelligence as an enabler of enhanced financial strategy and sustainability. While Artificial Intelligence is not empirically tested as a quantitative variable in this study, its theoretical integration is examined to understand how it may augment decision-making processes and strengthen the effectiveness of financial strategies in achieving sustainable outcomes. The study addresses key gaps in existing literature, which often isolates financial metrics from sustainability outcomes and neglects the revolutionary impact on industrial financial management. Using an empirical framework, the study tests multiple hypotheses to assess the significance of financial variables on sustainable financial performance and provides a conceptual model for Artificial Intelligence-enabled strategic finance. It is anticipated that the results will contribute to both scholarly knowledge and real-world implementations, assisting businesses in creating technologically advanced and robust financial plans that support sustainability goals.